Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

A novel friction self-centering damper using nitrogen gas springs: Development, experiments, and seismic response control - Chengyu Bai; Jianyang Xue; Zheng Luo; Rui Liu; Sha Ding (Engineering Structures, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Construction and application of controlled-release preservation pads based on Zein/sodium caseinate-stabilized oregano essential oil Pickering emulsions - Liu Yang; Wenwen Chen; Xinyu Zhang; Rui Xiao; Xue Ding; Zhipeng Jing; Hongyuan Zhang (Food Hydrocolloids, 2026)

Identification of novel B-cell neutralizing epitopes in goose Astrovirus type 2 - Shichao Yuan; Rui Fu; Bangfeng Xu; Wenqing Wang; Huamao Ding; Xue Pan; Chunxiu Yuan; Qinfang Liu; Zhifei Zhang; Qiaoyang Teng; Xiaona Shi; Minghao Yan; et al. (Veterinary Microbiology, 2026)

Using encapsulated essential oils to control food spoilage: encapsulation techniques, release methods, and preservation strategies-A comprehensive review - Rui Xiao; Yin Feng; Xinyu Zhang; Zhipeng Jiang; Wenwen Chen; Xue Ding; Gang Yang; Liu Yang (Food Control, 2026)

Three-Dimensional Numerical Simulation of Vertical Bearing Behaviour of Snowflake Vinyl Plastic Pile - Lei Gao; Mohammad Biplab Mia; Ding Lu; Rui Xue; Xuejian Gao (Geotechnical and Geological Engineering, 2025)

Sediment amplifies organic matter cycling and nutrients feedback in eutrophic lake zones - Junfeng Xing; Yuping Zhou; Ding He; Fen Guo; Penghui Li; Yuan Zhang; Rui Lv; Runze Xue; Changqing Liu; Yihua Xiao (Water Research, 2025)

Catalytic dehydrogenation of propane by electrospinning one-dimensional Zn-Ga2O3-Al2O3 nanofibres under CO2 atmosphere - Rui Chen; Xue Han; Yixuan Yang; Xupeng Yang; Yuqi Wang; Yupeng Zhang; Tiange Huang; Jie Wei; Junjie Ding; Xuyu Wang; Hongbing Ji (Fuel, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

From a metabolomics profiling perspective explaining the deterioration impact induced by chicken meat exudate - Ruilin Xu; Rui Ding; Xuankai Zheng; Junhua Shao; Xinglian Xu; Xue Zhao (Food Chemistry, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Recovery of boron and zinc from wastewater via electrodialytic metathesis - Mingzhi Lv; Yaoxing Liu; Jie Jiang; Rui Lian; Hun Xue; Riyao Chen; Rui Ding; Jianxi Liu (Desalination, 2024)

Polystyrene shell-based “coconut-like” and “pomegranate-like” microencapsulated phase change materials: Formation mechanism, thermal conductivity/stability enhancement and their application in thermal management - Wei Zhang; Rui Pan; Jihua Yang; Mengru Liu; Yunle Yao; Awang Zhang; Yi Gong; Zhengya Gan; Rui Hu; Jianjun Ding; Lin Chen; Xian Zhang; et al. (Chemical Engineering Journal, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Framework of land use planning for an energy producing city of Northwest China based on water-energy-food nexus - Zhou Fang; Shi Xue; Changgao Cheng; Qin Zhou; Maroof Ali; Rui Xu; Jinxue Xu; Tonghui Ding; Jie Wang; Zhongde Huang; Xiping Sun; Yang Bai (Journal of Cleaner Production, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

TRPML1 contributes to antimony-induced nephrotoxicity by initiating ferroptosis via chaperone-mediated autophagy - Lei Liu; Chao Luo; Dongnan Zheng; Xuehai Wang; Rui Wang; Wenjie Ding; Zhaoping Shen; Peng Xue; Shali Yu; Yifei Liu; Xinyuan Zhao (Food and Chemical Toxicology, 2024)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Contamination profile and risk assessment of per- and polyfluoroalkyl substances in Guanting Reservoir, a former drinking water source with degraded water quality - Tong Qi; Rui Guo; Shuai Ding; Chengyou Liu; Xue Li; Xiaocui Qiao; Yan Liu (Journal of Water Process Engineering, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Heterogeneity of molecular-level and photochemical of dissolved organic matter derived from decomposing submerged macrophyte and algae - Jia He; Lixin Jiao; Guoqiang Zhi; Xue Wu; Yan Yang; Shuai Ding; Jinlong Zheng; Zhi Shao; Rui Xia (Journal of Environmental Management, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Influencing mechanisms of gas bubbles on propagation characteristics of leakage acoustic waves in gas-liquid two-phase flow - Yuan Xue; Linjing Yue; Rui Ding; Shufang Zhu; Cuiwei Liu; Yuxing Li (Ocean Engineering, 2023)

Effects of calcination on the environmental behavior of sediments by phosphorus speciation and interface characterization - Rui Xia; Pingzhou Duan; Rui Li; Lixin Jiao; Jia He; Shuai Ding; Xue Wu (Journal of Environmental Management, 2023)

Evaluation of the pathogenesis of non-typical strain with α-hemolysin, Vibrio parahaemolyticus 353, isolated from Chinese seafood through comparative genome and transcriptome analysis - Fei Zha; Rui Pang; Shixuan Huang; Jumei Zhang; Juan Wang; Moutong Chen; Liang Xue; Qinghua Ye; Shi Wu; Meiyan Yang; Qihui Gu; Yu Ding; et al. (Marine Pollution Bulletin, 2023)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

De Novo Assembled Transcriptome Analysis and Identification of Genic SSR Markers in Red-Flowered Strawberry - Yan Ding; Li Xue; Rui-xue Guo; Gang-jun Luo; Yu-tong Song; Jia-jun Lei (Biochemical Genetics, 2019)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Phylogenetic relationships between Leymus (Poaceae, Triticeae) and related diploid Triticeae species based on isozyme and genome-specific random amplified polymorphic DNA (RAPD) markers - Rui-Wu Yang; Min-Han Zhong; Xue-Mei Zou; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou (Plant Biosystems, 2012)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)